Food Anticipatory Activity on Circadian Time Scales Is Not Dependent on Central Serotonin: Evidence From Tryptophan Hydroxylase-2 and Serotonin Transporter Knockout Mice - Gallardo, Christian M.; Martin, Camille S.; Steele, Andrew D. (Frontiers in Molecular Neuroscience, 2020)
A number of studies implicate biogenic amines in regulating circadian rhythms. In particular, dopamine and serotonin influence the entrainment of circadian rhythms to daily food availability. To study circadian entrainment to feeding, food availability is typically restricted to a short period within the light cycle daily. This results in a notable increase in pre-meal activity, termed ‘food anticipatory activity’ (FAA), which typically develops within about one week of scheduled feeding. Several studies have implicated serotonin as a negative regulator of FAA: 1) aged rats treated with serotonin 5-HT2 and 3 receptor antagonists showed enhanced FAA, 2) mice lacking for the 2C serotonin receptor demonstrate enhanced FAA, and 3) pharmacologically increased serotonin levels suppressed FAA while decreased serotonin levels enhanced FAA in mice. We sought to confirm and extend these findings using genetic models with impairments in central serotonin production or re-uptake, but were surprised to find that both serotonin transporter (Slc6a4) and tryptophan hydroxylase-2 knockout mice demonstrated a normal behavioral response to timed, calorie restricted feeding. Our data suggest that FAA is largely independent of central serotonin and/or serotonin reuptake and that serotonin may not be a robust negative regulator of FAA.